Taxonomic investigation of the Xanthium strumarium L. complex (Asteraceae) distributed in Iran inferred from morphological, palynological and molecular data - Fariba Noedoost; JAMIL VAEZI; SEDIGHEH NIKZAT SIAHKOLAEE (Society for Indonesian Biodiversity, 2021)
Abstract. Noedoost F, Vaezi J, Nikzat Siahkolaee S. 2021. Taxonomic investigation of the Xanthium strumarium L. complex (Asteraceae) distributed in Iran inferred from morphological, palynological and molecular data. Biodiversitas 22: 1961-1974. Unclear species boundaries due to high morphological similarities lead to different opinions on Xanthium classification. To solve this problem, we conducted investigation on morphological, palynological and molecular (ITS sequencing) of three species of Xanthium (i.e., X. strumarium, X. sibiricum, and X. brasilicum) forming Xanthium strumarium complex in Iran. We randomly collected 110 plant individuals of the Xanthium strumarium complex as well as X. spinosum from 30 geographical populations in eight provinces of Iran. Pollen grains of 19 populations were studied by scanning electron microscope (SEM). Results obtained from the analysis of morphological characters showed that the three species, X. strumarium, X. brasilicum and X. sibiricum were placed nearly together specially X. strumarium and X. brasilicum are obviously overlapped. Palynological results indicated the pollen grains of section Acanthoxanthium (i.e., X. spinosum) and Xanthium (i.e., X. strumarium, X. sibiricum, and X. brasilicum) are clearly differing by their LM and SEM characters. However, no significant difference found between the pollen of X. strumarium and X. brasilicum. The Bayesian phylogenetic tree of the ITS region of rDNA sequences revealed that X. strumarium, X. sibiricum and X. brasilicum could not be discriminated as independent species. Overall, the morphological, palynological and molecular data provided evidence to synonymize X. brasilicum and X. strumarium with X. orientale and X. sibiricum with X. strumarium.